Clinical, Magnetic Resonance Imaging and Treatment Features in Orbital Cavernous Hemangiomas - Rövşen Nesirov; Kaan Gündüz; Esra Erden (Türk Oftalmoloji Dergisi)
Objectives: To report the clinical, magnetic resonance imaging (MRI), and treatment features in cases of orbital cavernous hemangioma. Materials and Methods: TThe records of 32 patients with orbital cavernous hemangioma operated in the Department of Ophthalmology at Ankara University School of Medicine from June 1998 to April 2013 were reviewed retrospectively. Results: Twenty-three patients were female and 9 patients were male. The mean age was 42 years, ranging from 9 to 62 years. In MRI of 21 patients, all tumors were isointense to muscle in T1A-weighted images, hyperintense to muscle in T2A-weighted images, and demonstrated heterogeneous contrast enhancement. The tumor was intraconal in 13 patients, superomedial in 3 patients, superotemporal in 3 patients, and inferomedial in 2 patients. In all patients, orbitotomy was performed and the orbital mass was totally removed in one piece. The endoscopic approach used was as follows; upper temporal in 13 patients, inferior temporal in 10, upper nasal in 8, and transnasal orbitotomy in 1 patient. In all patients, no residual/recurrent mass was found after surgery. In eighteen patients, visual acuity remained the same before and after surgery. In fourteen patients, mean visual acuity at first month after surgery increased to 0.10±0.14 logMAR, while mean visual acuity before surgery was 0.25±0.21 LogMAR (p<0.01). Conclusion: In patients with orbital cavernous hemangioma, a presumptive diagnosis can be made by clinical and radiological findings. Anterior orbitotomy through a skin incision was used in most patients with orbital cavernous hemangioma in this series. Significant improvement in visual acuity and examination findings were observed after surgery in patients with orbital cavernous hemangioma. (Turk J Ophthalmol 2015; 45: 105-110)